Cultural identifications of the Greek Orthodox elite of Constantinople: discourse on music in the nineteenth and early twentieth centuries - Erol, Merih. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This dissertation aims to explore the formation of a musical discourse among the Greek Orthodox educated elite of Constantinople in the nineteenth and early twentieth centuries. This discourse was formed mainly through the practices and activities of the voluntary music associations and the debates on musicological issues in the columns of the Greek dailies and journals. This study analyzes the musical discourse within the issues of cultural nationalism, national and social identity formation and modernization. Particular attention is paid to the investigation of the musical discourse in its historical context, namely the social, economic and political transformations that the Orthodox millet underwent in the post-Reform Edict (1856) period, and the prospects of certain political and ideological schemes that became potentially available in this era. Furthermore, by uncovering the plurality of discourses, definitions and views pertaining to cultural identity and musical debates, this dissertation aims to contribute to the challenging of the standard approach which sees the Greek Orthodox millet as a monolithic unit. The main body of sources used in this dissertation consists of treatises on music, essays on music in periodicals and newspapers, speeches, patriarchal circulars, the statutes of musical associations and the prologues of the collections of ecclesiastical chants, popular and folk songs. The archives of the Patriarchate of Constantinople, the Greek Orthodox Community of Stavrodromio (Beyoğlu), the Asia Minor Association ‘East’ and the Ottoman archive were used in this study.
Keywords: Group identity.